(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2021)
Over the last 18 months, the Sars-Cov-2 pandemia has heavily worsened indicators of poverty, unemployment and social exclusion. At the same time the number of episodes of domestic violence increased as a consequence of the restrictions imposed by the governments to prevent people from contagion. This article tries to answer to some research questions concerning the strategies adopted by both public institutions and the anti-violence shelters to continue supporting women victims of violence notwithstanding the personal movement restrictions. The study analyzes some relevant aspects emerging from the situation of Italy and Argentina, two countries that share some cultural, historical, and economical characteristics, and whose public institutions seem to have adopted similar strategies to cope with the phenomenon of violence against women during the most critical phase of the pandemia. The authors of the study have adopted a qualitative methodology, based on in depth interviews to key informants (operators, responsible of shelters), in a period ranging from the second semester of 2020 and the first three months of 2021. Through the evidences of their experiences it was possible to identify the innovations introduced by the operators to overcome the obstacles to women’s assistance posed by the pandemia.